2022
DOI: 10.1101/2022.11.04.514813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microplastics are present in women’s and cows’ follicular fluid and polystyrene microplastics compromise bovine oocyte functionin vitro

Abstract: Decades of careless use and improper disposal have resulted in plastic pollution accumulating almost everywhere on earth, yet the health implications of the billions of tons of plastic pollution scattered across the planet's terrestrial ecosystems are largely unknown. We show that microplastics are present in the follicular fluid of women and domestic cows. We found that the concentrations of microplastics that naturally occurred in follicular fluid were sufficient to compromise the normal functioning of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 74 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Organisms can digest particles smaller than 150 µm, which may then pass through the intestinal wall and enter lymph nodes and other body organs (10). Recent reports suggested that MPs can accumulate in humans' lungs and digestive tract and then be scattered into blood, placenta, and female follicular fluid (11)(12)(13). In wastewater and surface sediments, polystyrene MPs (PSMPs) are the most often found MPs (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Organisms can digest particles smaller than 150 µm, which may then pass through the intestinal wall and enter lymph nodes and other body organs (10). Recent reports suggested that MPs can accumulate in humans' lungs and digestive tract and then be scattered into blood, placenta, and female follicular fluid (11)(12)(13). In wastewater and surface sediments, polystyrene MPs (PSMPs) are the most often found MPs (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Following Grechi et al (2022), a confocal Raman spectroscope (alpha300 R, WITec, Germany) with a spectrometer (UHTS 300, WITec, Germany), and a 532 nm laser was used for the characterization of the microplastics. The microscope was operated by using the Control Five software, which allowed the imaging of the whole membrane area using a ×50 NA 0.75 Zeiss objective.…”
Section: Analysis Of Isolated Microplastics By Confocal Raman Spectro...mentioning
confidence: 99%
“…The lowest fibre detection was in the laminar flow filters (3.7%), while 50% of the fume hood samples presented microfiber contamination. To demonstrate the importance of reliable, low-contamination blanks, we used raw data on the number of MPs detected in a human follicular fluid sample from Grechi et al (2022) that was processed in a laminar flow. We then adjusted the MPs concentration in this sample to the 9 blanks we investigated here, as well as to the original blank from Grechi et al (2022) that was produced in parallel to the sample processing.…”
Section: Laboratory Mps Contamination Is a Reality That Needs To Be T...mentioning
confidence: 99%
See 2 more Smart Citations